Edukasi Sekolah Hijau (Green School) untuk Menanamkan Karakter Peduli Lingkungan Pada Siswa Sekolah Dasar - Rosnaningsih, Asih; Syah Putra, Aidil (Apik Cahaya Ilmu, 2025)
This activity aims to provide education to instil environmental awareness and caring character in elementary school students. The method used in this research is participatory qualitative, involving all school members, including students, teachers, parents, or guardians, through integrative thematic activities with an environmental theme. Specifically, the target participants in this activity were upper-grade students (grades 4-6), totalling 86 students. The instruments used in this study included observation guidelines, documentation guidelines, and student perception questionnaires. The research results indicate that the forms of education that can be implemented consist of three types of activities: (1) integrating the green school concept into the curriculum, (2) developing environmental care character through school habituation, and (3) establishing collaboration between the school and various stakeholders. Overall, the results of these community service activities show that the implementation of environmental education in schools, both through curriculum integration, daily habits, and support from the school's social environment, has a positive impact on the formation of environmentally conscious character in students. It is suggested that schools strengthen the implementation of environmental education within the green school program in an integrated and sustainable manner through learning, habituation, and cross-sector partnerships.